Imprensa e música no Brasil: rock, mpb e contracultura no período Rolling Stone - 1972 - Sberni Junior, Cleber [UNESP] (2015)
The aim of the present study was to assess the issues of Rolling Stone edited in Brazil between December 1971 and January 1973. More specifically, the goal was to evaluate how the magazine integrates the Rio de Janeiro's rock scene in the early 1970s, promoting and doing record of artistic activities, thus contributing to the dissemination of rock made in Brazil. The analyzed period is characterized by a striking cross-country youthful movement influenced by counterculture, whose ideology was conveyed via music, books, and publications. This historical period also witnessed the development of the market of symbolic goods in Brazil, boosting the recording industry, which was going through a cycle of expansion and selfassurance, and of the market of periodical publications, which was also on the rise. It was in that context that Rolling Stone, aimed at a young readership and incorporating the distinctive features of a specialized magazine, hit the newsstands, covering information and news on rock, MPB (Brazilian popular music), and counterculture. Actually, the predominant genres were international rock, rock made in Brazil, and MPB influenced by tropicalism. During its short-lived existence, 36 issues were sold at newsstands, having a nationwide circulation and providing an overview of the musical scene by means of articles, interviews, and album reviews. The texts published in the magazine demonstrated a close relationship between rock and MPB. There was an all-out effort channeled into giving visibility to the activity of new rock bands and artists who attached a high value to counterculture and to its interaction with rock. It is also possible to claim that the magazine was an integral part of the musical scene it helped establish, evoking moments, placing a high value on experiences and on musical events, and making room for rock bands and rock itself. In short, Rolling Stone eventually strengthened...